Aktivitas Cyber PR melalui Podcast Juara (Jabarprov Bersuara) - Agustine, Deva Adelya; Fakhruroji, Mochammad; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe the stages of cyber PR activities through the Champion podcast (Jabarprov Bervoice) using the concept of The Circullar Model of Some for Social Communication from Regina Luttrell. This study used a qualitative descriptive method with collection techniques through in-depth interviews, observation, and documentation studies. The research results obtained are; first, the share stage of Diskominfo Jabar's public relations information increases public participation (participate), connects with the public (connect) and builds public trust (build trust) through shared content, second, the stage optimizes (optimizes) the message of Public Relations Diskominfo Jabar pays attention to the characteristics the public, being part of the public conversation, third, the stage of managing (managing) public relations information Diskominfo Jabar performs media monitoring in disseminating content, providing quick responses, real-time interaction with the public, and fourth, the stage of engaging (involving) the public : public relations Diskominfo Jabar is affiliated with the Governor of West Java, knows the whereabouts of the audience and holds joint activities with the public.